Unveiling nitrogen oxide emissions from open-pit copper mines through satellite observations - Ialongo, Iolanda; Virta, Henrik; Hakkarainen, Janne; Özcan, Cem; Ranta, Mikko; Zieleniewski, Simon (Institute of physics publishing, 2025)
Copper is a critical mineral for clean energy and transportation, and it is necessary for a sustainable economy that aims at reducing fossil fuel usage. Assessing the performance and environmental impacts of copper mining is therefore necessary to evaluate the progress towards sustainable development. In this study, we estimate the nitrogen oxide (NOx) emissions (largely attributable to the diesel-powered mobile fleet) over 14 of the world's largest open-pit copper mines. We derive the emissions by applying a data-driven approach to the satellite-based nitrogen dioxide (NO2) observations from the TROPOspheric Monitoring Instrument on board the Sentinel-5 Precursor satellite. We find that the annual NOx emissions over the different mines are coupled to the corresponding copper production, ore processed and total material moved. The time series analysis reveals that the annual amount of total material moved over the open pit of each mine best reproduces the year-to-year variability of the NOx emissions. Overall, satellite NO2 observations show good potential in tracking mining activities and for improving the assessment of the environmental impact of the mining industry.
Keywords: copper mining; TROPOMI; nitrogen dioxide; emissions; nitrogen oxides; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|